Proceedings of the 12th International Conference on Intelligent User Interfaces 2007
DOI: 10.1145/1216295.1216355
|View full text |Cite
|
Sign up to set email alerts
|

Modelling personality in voices of talking products through prosodic parameters

Abstract: In this paper we report preliminary findings from two user studies that on the one hand investigate how prosodic parameters of synthetic speech can influence the perceived impression of the speakers personality and on the other hand explores if and how people attribute personality to objects such as typical products of daily shopping. The results show that a) prosodic parameters have a strong influence on the perceived personality and can be partially used to achieve a desired impression and b) that subjects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Therefore, speech data should allow one to perform APP reasonably well. While still being limited, the results proposed so far in the speech literature seem to confirm the indications above for both APR (Mairesse et al, 2007;Ivanov et al, 2011) and APP (Mairesse et al, 2007;Mohammadi and Vinciarelli, 2012;Polzehl et al, 2010;Valente et al, 2012;Nass and Min Lee, 2001;Schmitz et al, 2007;Trouvain et al, 2006).…”
Section: Speaker Personalitysupporting
confidence: 54%
See 2 more Smart Citations
“…Therefore, speech data should allow one to perform APP reasonably well. While still being limited, the results proposed so far in the speech literature seem to confirm the indications above for both APR (Mairesse et al, 2007;Ivanov et al, 2011) and APP (Mairesse et al, 2007;Mohammadi and Vinciarelli, 2012;Polzehl et al, 2010;Valente et al, 2012;Nass and Min Lee, 2001;Schmitz et al, 2007;Trouvain et al, 2006).…”
Section: Speaker Personalitysupporting
confidence: 54%
“…Such an effect, known as similarity-attraction, takes place between humans as well ) and seems to suggest that people do not make differences, at an unconscious level, between real and artificial voices. In the same vein, the experiments proposed by Schmitz et al (2007) and Trouvain et al (2006) show that it is possible to elicit the attribution of predefined traits by changing the characteristics of artificial voices (36 assessors were involved in the tests).…”
Section: Speaker Personalitymentioning
confidence: 95%
See 1 more Smart Citation
“…We changed the four prosodic parameters pitch range (in semitones), pitch level (in Hz), tempo (as a durational factor in ms), and intensity (soft, modal, or loud as in [57]) according to our literature review [55]. For example, a competent voice has a higher pitch range (8 semitones), a lower pitch level (-30%), a 30% higher tempo, and a loud intesity compared to the baseline voice.…”
Section: Modelling Personality In Voicesmentioning
confidence: 99%
“…For example, a competent voice has a higher pitch range (8 semitones), a lower pitch level (-30%), a 30% higher tempo, and a loud intesity compared to the baseline voice. In [55] we also evaluated whether it is possible to model different personalities with the same voice by adjusting these prosodic parameters, such that listeners will recognize the intended personality dimension. The study has shown that there are clear preferences for our prosody-modeled speech synthesis for certain brand personality dimensions.…”
Section: Modelling Personality In Voicesmentioning
confidence: 99%